2013
DOI: 10.1080/00223891.2013.825624
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Personality Pathology Associated With Major Depressive Episodes: Incremental Validity of Informant Reports

Abstract: Major limitations are associated with the use of a single source of information to assess personality pathology. The construct validity of standardized interviews and informant reports on personality pathology has been established relative to other measures of personality pathology, but it is also important to consider these measures in relation to other constructs that should be related to personality pathology. One example is major depression. In this study, we evaluated whether less common clinical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
(52 reference statements)
1
14
0
2
Order By: Relevance
“…Historically, this work has largely relied on subjective self-reports to assess personality, perhaps because researchers previously have questioned the value of collateral informants (e.g., spouse, coworker) in terms of cost, psychometric properties, incremental value (i.e., relative to self-reports), and compliance with completing reports that assess others’ personality traits (for a review, see Vazire, 2006). Importantly, a great deal of research in these areas now indicates that collateral informants’ personality reports (a) can provide cost-efficient, reliable, and valid information about others’ personality traits; (b) can be administered via multiple formats (e.g., in-person clinical assessments, online assessments); and (c) predict variance in external criterion variables over-and-above self-report personality measures (e.g., Balsis, Cooper, & Oltmanns, 2015; Galione & Oltmanns, 2013; Vazire & Mehl, 2008). Yet, with some exceptions (cf.…”
Section: Research and Theoretical Implicationsmentioning
confidence: 99%
“…Historically, this work has largely relied on subjective self-reports to assess personality, perhaps because researchers previously have questioned the value of collateral informants (e.g., spouse, coworker) in terms of cost, psychometric properties, incremental value (i.e., relative to self-reports), and compliance with completing reports that assess others’ personality traits (for a review, see Vazire, 2006). Importantly, a great deal of research in these areas now indicates that collateral informants’ personality reports (a) can provide cost-efficient, reliable, and valid information about others’ personality traits; (b) can be administered via multiple formats (e.g., in-person clinical assessments, online assessments); and (c) predict variance in external criterion variables over-and-above self-report personality measures (e.g., Balsis, Cooper, & Oltmanns, 2015; Galione & Oltmanns, 2013; Vazire & Mehl, 2008). Yet, with some exceptions (cf.…”
Section: Research and Theoretical Implicationsmentioning
confidence: 99%
“…Neither source is necessarily more valid than the other. Incremental validity analyses have even demonstrated that-for some purposes and under certain conditions-informant-reports of personality disorder traits predict behavior and consequential outcomes over and above self-reports (Cruitt & Oltmanns, 2018;Galione & Oltmanns, 2013;Ready, Watson, & Clark, 2002). For example, informant-reports of personality disorder traits are predictive of targets' dismissal from the military (Fiedler et al, 2004), neutralobserver behavioral ratings (Kaurin et al, 2018), and social adjustment (Klein, 2003) over and above self-reports.…”
Section: Self-other Agreement On Ratings Of Personality Disorder Sympmentioning
confidence: 99%
“…In the clinical domain, research has further revealed that informant ratings of targets' (patients') personality disorder features or maladaptive personality traits, respectively, contribute uniquely to the prediction of future depressive symptomatology, personality disorders, and general social functioning of targets (Galione & Oltmanns, 2013;Klein, 2003;Lawton, Shields, & Oltmanns, 2011;Ready, Watson, & Clark, 2002). Likewise, informant reports of military recruits' personality disorder features yielded incremental accuracy for the prediction of early discharge from military (Fiedler, Oltmanns, & Turkheimer, 2004).…”
Section: Unique Predictive Accuracy Of Informant Reportsmentioning
confidence: 99%